Cyberbiosecurity: Advancements in DNA-based information security - Tuoyu Liu; Sijie Zhou; Tao Wang; Yue Teng (Elsevier, 2024)
Synthetic biology is a crucial component of the "cyber-biological revolution" in this new industrial revolution. Owing to breakthroughs in synthetic biology, deoxyribonucleic acid (DNA), the storehouse of hereditary material in biological systems, can now be used as a medium for storage (synthesis) and reading (sequencing) of information. However, integrating synthetic biology with computerization has also caused cyberbiosecurity concerns, encompassing biosecurity and information security issues. Malicious codes intended to attack computer systems can be stored as artificially synthesized DNA fragments, which can be released during DNA sequencing and decoding and attack computer and network systems. As these cyberbiosecurity threats become increasingly realistic, spreading awareness and information about how they can be prevented and controlled is crucial. This review aims to address this need by offering crucial theoretical backing for cyberbiosecurity research and raising awareness of risk mitigation and control measures in information security, biosecurity, and national security.